Konservasi Lingkungan Berbasis Kearifan Lokal di Wilayah Cagar Alam Rawa Danau - Ertando, Alfi; Zulkarnaen, Zulkarnaen; Utami, Noviani; Yulianty, Sindanita; Putri, Amalianneisha Rafadewi Andhanatami; Agustina, Ika (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Environmental conservation based on local wisdom plays a crucial role in maintaining ecosystem balance and supporting the achievement of the Sustainable Development Goals (SDGs). The Rawa Danau Nature Reserve in Serang Regency is an area with high biodiversity that is still preserved through the traditional practices of the local community. This study aims to explore the forms of environmental conservation based on local wisdom in this area. The research uses a qualitative approach with an ethnographic method that involves observation, interviews, and literature review. The research results indicate that the communities surrounding the Rawa Danau Nature Reserve apply local wisdom values in the form of customary rules, such as prohibitions on using engines in Rawa Danau waters, entering sacred areas, and excessive exploitation like picking branches, as well as ecological myths about wild animals that function to regulate the use of natural resources and maintain ecosystem balance. The integration of local wisdom values into conservation policies can enhance the sustainability of area management while simultaneously strengthening the role of local communities in environmental preservation.